2019
DOI: 10.1007/s00216-019-01732-2
|View full text |Cite
|
Sign up to set email alerts
|

Analytical chemistry with biosolvents

Marek Tobiszewski

Abstract: One of the current trends in green analytical chemistry is the introduction of green solvents, some of which are biobased. At the same time, the development of the biorefinery concept has allowed more biochemicals to be obtained with increased efficiency and from a wider range of feedstocks. The first examples of the use of biosolvents in analytical applications included extractions performed with alcohols, esters, and terpenes. However, many more applications of biosolvents in extractions of bioactive compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…However, addition of concentrated NaOH (10e20 M) was required to trigger phase separation. Recent reviews devoted to the application of greener solvents in analytical chemistry can be found [16,17].…”
Section: Implementation Of Novel Materials In Sample Preparationmentioning
confidence: 99%
“…However, addition of concentrated NaOH (10e20 M) was required to trigger phase separation. Recent reviews devoted to the application of greener solvents in analytical chemistry can be found [16,17].…”
Section: Implementation Of Novel Materials In Sample Preparationmentioning
confidence: 99%
“…Ethyl lactate garnered by corn and soybeans through the fermentation of biomass and the reaction of two fermentation products, ethanol and lactic acid. Ethyl lactate is mainly used in the extraction of phytochemicals (37). Although extremely promising, it should be noted that not all biobased solvents are of no environmental consequence.…”
Section: Materials Of Biological Originmentioning
confidence: 99%
“…Although extremely promising, it should be noted that not all biobased solvents are of no environmental consequence. For example, terpenes are toxic to fish, while obtaining acetic acid from corn carbohydrate leads to higher emissions of greenhouse gasses than the production of its' fossil fuel-based counterpart (37).…”
Section: Materials Of Biological Originmentioning
confidence: 99%
“…Despite the advantages, these solvents are still poorly explored as the extraction phase for microextraction techniques, mainly with chromatography techniques. Some drawbacks may have to be overcome, such as the high viscosity that causes poor analyte mass transfer and also the incompatibility with analytical instrumentation [91]. Nevertheless, an alternative would be their combination with other green solvents or their use as modifiers of solid sorbents, as already proposed by Hashemi et al (2018) [63].…”
Section: Bio-based Solventsmentioning
confidence: 99%